The Scarborough Shoal dispute in America’s Asia-Pacific pivot - Samaniego, Catherine (2012)
The intensifying tension between China and the Philippines over Scarborough Shoal calls for an impartial intervention from the US. The peaceful resolution of the dispute lies in how the US successfully maneuvers between its traditional ally and its biggest competitor.